PERKEMBANGAN AGAMA SIKH DI KOTA MEDAN SUMATERA UTARA - Fitriani, Fitriani (Studia Sosia Religia, 2022)
Freedom of religion in Indonesia is a right that must be owned by the Indonesian nation. Apart from the six recognized religions in Indonesia, the Sikh religion is one of them. The Punjabi people who follow the Sikh religion are part of the ethnic diversity found in Indonesia, especially in the city of Medan. Although the Sikh religion is not an official religion, it is still accepted and growing in Indonesia, especially in the city of Medan, North Sumatra. In the development of religious studies, the Sikh religion is included in the top ten religions in the world. However, the importance of this study is studied, seeing that its development is still able to maintain its existence among the Muslim minority. This type of research is field research using a religious history approach, trying to see the process of development that occurred in the Sikh religion. The results of these findings show that the spread of the Sikh religion in Indonesia can be said to be growing with an increasing number of adherents. evidenced by several buildings of houses of worship for the Sikh religion, namely Gurdwara Shree at several points in Medan City including, Gurdwara Perbhandak on Jalan Teuku Umar, Gurdwara Shree Guru Tegh Bahadur area on Jalan Polonia and Gurdwara Shree Guru Nanak Dev Ji on Jalan Karya Murni. Factors causing the Sikh religion to continue to grow are because the Sikh religion does not recognize caste which results in social inequality for its adherents. Moreover, the Sikh religion is able to live side by side in the midst of the majority.